A ficção histórica em Vigilia del Almirante, de Augusto Roa Bastos - Pimenta, Larissa Itami O’Hara (2015)
Analyzes the work Vigilia del Almirante, Augusto Roa Bastos's, published in 1992 in his most striking textual aspects, from the procedures used by the writer to the creation of the historiographical metafiction, which the author reveals himself to be the result of the fifth centennial celebration from the voyage of Christopher Columbus to America. Seeks, in filling the gaps left by the history of the discovery, understanding the making of a fictional Columbus. The particular truth of the studied fiction allows us to build and deconstruct the parody of the main character. The work of Roa Bastos invades the history and resumes Columbus figure of poetic and revisional mode. Concepts such as "historical novel", "mimesis", "likelihood," "defamiliarization" and others are addressed to the interpretation of the text. Also, the categories of romance are perceived in this study, as characters, time, space and plot, beyond the particularities of the genre in question.